(untitled) (Journal of Philosophy Culture and Political Science, 2021)
Currently, among the world’s diasporas, the Chinese diaspora called «Huaqiao» is considered the most numerous. More than 50 million representatives of the Chinese Huaqiao live in more than 150 countries around the world. Since the beginning of the policy of openness and reform, the Chinese leadership has paid great attention to working with the Chinese diaspora, and the Communist Party of China (CPC) has realized how high its potential is. Because, migration processes are the most important direction of modern state policy. In this article, the authors will consider the contribution of «huaqiao» to the revival of the People’s Republic of China, recognized as a «Chinese miracle», and the specifics of the policy of the Chinese authorities on interaction with the foreign Chinese diaspora. The article presents a political analysis of the emigration flows of the Chinese population to the countries of the world in the context of globalization, the peculiarities of the internal consolidation of foreign Chinese and their entry into the host society, the interaction of the Chinese diaspora with their historical homeland and the impact on the political and economic modernization of the PRC. Summarizing the experience of the foreign Chinese diaspora and the migration policy of the People’s Republic of China, we can draw lessons for Kazakhstan. Based on the Chinese experience, the potential force that can contribute to the development of Kazakhstan is the Kazakh diaspora, whose number is about five million people living in different countries of the world, topical issues are raised from spiritual and cultural interaction with foreign Kazakhs to the establishment of economic cooperation, proposals are given that contribute to the development of work in this direction. Key words: migration policy, national policy, diaspora, irridenta, «huaqiao», cooperation, historical homeland, repatriation, compatriots.of the world, topical issues are raised from spiritual and cultural interaction with foreign Kazakhs to the establishment of economic cooperation, proposals are given that contribute to the development of work in this direction. Key words: migration policy, national policy, diaspora, irridenta, «huaqiao», cooperation, historical homeland, repatriation, compatriots.